Taiwanese Dermatological Association consensus statement on management of psoriasis - Tsen-Fang Tsai; Chih-Hung Lee; Yu-Huei Huang; Ching-Chi Chi; Yun-Ting Chang; Tak-Wah Wong; Chih-Hsun Yang; Li-Fang Wang (Wolters Kluwer Medknow Publications, 2017)
Background: Effective management of psoriasis is a cause for much concern. In Taiwan, there is a lack of consensus on management strategies for psoriasis, especially the principles of drug prescribing in psoriatic patients. Objectives: The Taiwanese Dermatological Association convened Expert Panel meetings three times between 2012 and 2015 to discuss the management strategies for treatment of psoriasis in order to fill the knowledge gap and provide a reference tool for Taiwanese dermatologists. Results: This paper reports the final output from the three meetings, with the aim of aiding clinical decision making in terms of principles of prescribing, including dosing strategies, efficacy profiles, and safety concerns in connection with eight categories of antipsoriatic treatment: topical agents, phototherapy, nonbiologic conventional systemic agents, licensed biologic systemic agents, newly emerging therapies, combination therapy, transitional therapy, and traditional Chinese medicine. Conclusion: The Expert Panel, comprising distinguished Taiwanese dermatologists, succeeded in developing a consensus about the management of psoriasis in Taiwanese patients. Unavailability of data in certain areas may suggest a possibility of new directions in research.